SOSIALISASI PANCASILA SILA KE-1 DENGAN MENGAJARKAN BACAAN SHOLAT DAN PRINSIP DASAR RUKUN ISLAM DAN RUKUN IMAN PADA SISWA SISWI SD JUARA JAKARTA UTARA UTARA - Yoka Mai Patra; Ana Chaerunisyah; Firdaus Suwarta; Ferena Athfannisa; Hidayat Hidayat (Gapenas Publisher, 2023)
Pancasila, as the foundation of the Indonesian state, emphasizes the importance of implementing moral and ethical values in societal life. One of the highly relevant values to highlight is the First Principle,